Excitations of waveguides and cavities by electron beams - A. A. Kurayev; A. O. Rak; A. V. Senko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The correct excitations equations for waveguides and cavities by electron beams in general case where 3D phase-modulating take place are formulated.